AGE AND GENDER PREDILECTION OF ORAL ULCERS IN AN OUTPATIENT POPULATION VISITING A DENTAL COLLEGE - K. , Thirumagal; S, Gheena.; Kumar Jain, Ravindra (International Journal of Psychosocial Rehabilitation, 2020)
Ulceration is due to defects in the epithelium or the underlying connective tissue, or both. The ulcer is classified on the basis of the duration as acute (ulcer present for short period of time) and chronic (ulcer present for a long period of time). Oral ulcers always occur commonly because of injury due to improper fitting dentures, cracked teeth, or restoration. The aim of the study is to find the age and gender predilection of oral ulcer in the outpatient population of Dental College. The study was conducted among the outpatients of a Dental College and Hospital. The data was reviewed and analyzed from the total number of 86000 patients between June 2019- March 2020. The data includes patient details like their gender, age, type of ulcer. which was manually verified by 1-2 reviewers and finally tabulated and analyzed by chi-square test (SPSS, IBM). Total subject population was 194 and their age ranges from (6-84) yrs. Male (63.9%) predilection was observed when compared to Female (36.1%) and predilection of Traumatic ulcer (60.8%) was seen when compared with that of recurrent aphthous ulcer (39.1%). Within the limitations of the study, the male predilection was observed when compared to females and predilection of traumatic ulcer was seen compared to recurrent aphthous ulcer among the study population.